2016
DOI: 10.1371/journal.pone.0165926
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Extracellular Vesicle Release from Human Cardiosphere Derived Cells with Lentiviral Knockdown of nSMase2 Differentially Effects Proliferation and Apoptosis in Cardiomyocytes, Fibroblasts and Endothelial Cells In Vitro

Abstract: Numerous studies have shown a beneficial effect of cardiosphere-derived cell (CDC) therapy on regeneration of injured myocardium. Paracrine signaling by CDC secreted exosomes may contribute to improved cardiac function. However, it has not yet been demonstrated by a genetic approach that exosome release contributes to the therapeutic effect of transplanted CDCs. By employing a lentiviral knockdown (KD) strategy against neutral spingomyelinase 2 (nSMase2), a crucial gene in exosome secretion, we have defined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…Similar results were reported after intramyocardial injection of human CDC exosomes in immunodeficient mice (30). Pharmacological blockade of exosome secretion by GW4869, which inhibits neutral spingomyelinase 2 [nSMase2; a crucial enzyme in exosome secretion (32)], nullified CDC bioactivity. Exosomes from both CPCs and CDCs were highly enriched with miR-146a, as compared with fibroblast exosomes (5,30).…”
Section: Visualization Of Exosome Release From Cpcssupporting
confidence: 74%
See 1 more Smart Citation
“…Similar results were reported after intramyocardial injection of human CDC exosomes in immunodeficient mice (30). Pharmacological blockade of exosome secretion by GW4869, which inhibits neutral spingomyelinase 2 [nSMase2; a crucial enzyme in exosome secretion (32)], nullified CDC bioactivity. Exosomes from both CPCs and CDCs were highly enriched with miR-146a, as compared with fibroblast exosomes (5,30).…”
Section: Visualization Of Exosome Release From Cpcssupporting
confidence: 74%
“…Using lentiviral knockdown of nSMase2, Lang et al (32) demonstrated that CDC exosomes contributed to the proangiogenic and promigratory activities of human CDCs in HUVECs while also reducing both apoptosis of cardiomyocytes and proliferation of fibroblasts in vitro. Chen et al (33) reported that mouse CPC exosomes inhibited cardiomyocyte apoptosis in mouse hearts after IR in vivo.…”
Section: Visualization Of Exosome Release From Cpcsmentioning
confidence: 99%
“…hCDCs have markers including CD90 and CD105 (mesenchymal markers), CD63 and HSP90 (exosomal markers), GATA4 and Nkx2.5 (markers of early cardiac development), and could be internalized by endothelial cells, cardiac fibroblasts, and myocytes. hCDCs exosomes could increase endothelial migration, tube formation, and branch point complexity, while reducing the human cardiac fibroblast proliferation (Lang, Young, Ashraf, & Canty, ). Secreted exosomes by cardiomyocytes in ischemic condition could increase mouse cardiac endothelial cell proliferation, endothelial cells migration, sprouting, and capillary‐like structures.…”
Section: The Role Of Exosome‐derived Components In Cardiovascular Funmentioning
confidence: 99%
“…Conditioned media from CDCs was enriched with RNA, the majority of which was contained within exosomes [88]. Co-culture of human CDCs with HUVECS was found to have proangiogenic effects that were not observed when exosome production was disrupted by nSmase2 knockdown in CDCs [89]. Injection of CDC derived exosomes in an acute MI mouse model mimicked the same benefits seen with injection of CDCs themselves [88]; the exosome treated hearts showed decreased scar mass and increased viable mass, as well as lower levels of pro-inflammatory cytokines, which may be a result of previously reported reduction in inflammatory macrophages by CDCs [90].…”
Section: Stem Cell Exosomes In Cardiac Treatmentmentioning
confidence: 99%